Hormonal and Temperature Manipulation to Produce Male Homogametic (XX) in Developing Female Monosex Culture of Thai Catfish Pangasionodon hypopthalmus - Arfah, H.; Carman, O. (Indonesian Society of Scientific Aquaculture (ISSA), 2008)
The female of Thai catfish Pangasionodon hypopthalmus had higher growth rate, about 25-30% than male fish, especially on growth phase-2 when the fish get sexually mature. Monosex female fish culture system can increase production efficiency in term of time and cost. Experiment was performed to get male homogametic (XX) that will be used as functional male to produce female monosex (XX) population Result of hormonal and temperature manipulation on larvae shown that the highest percentage of male (67.7%) was obtained by 5 mg/liter 17-α-metiltestosteron treatment with temperature 33oC. Good temperature for larva rearing was 30oC. The result of fertility test on male fish was fertile, but progeny test was not performed homogametic (XX) character yet. Keywords: hormonal manipulation, male homogametic XX, monosex, Pangasionodon hypopthalmus ABSTRAK Ikan patin Pangasionodon hypopthalmus betina memiliki laju pertumbuhan lebih cepat sekitar 25-30% daripada yang jantan, terutama pada fase pertumbuhan II saat ikan mulai matang kelamin. Budidaya ikan dengan sistem kultur monoseks ikan betina diduga akan meningkatkan efisiensi produksi dari segi waktu dan biaya. Penelitian ini bertujuan mendapatkan jantan homogametik (XX) yang akan dimanfaatkan sebagai jantan fungsional untuk menghasilkan populasi monoseks betina (XX). Hasil manipulasi hormon dan suhu terhadap larva ikan patin menunjukkan bahwa presentase kelamin jantan tertinggi (67,7%) terjadi dengan dosis perendaman dalam hormone 17-α metiltestosteron 5 mg/liter dengan suhu inkubasi 33oC. Suhu yang baik untuk pemeliharaan larva ialah 30oC. Hasil uji fertilitas terhadap induk jantan bersifat fertile, namun uji progeny belum dapat menunjukkan sifat homogametik (XX). Kata kunci : manipulasi hormonal, jantan homogametik (XX), monoseks betina, ikan patin, Pangasionodon hypopthalmus